A transition metal-free approach towards synthesis of β-carboline tethered 1, 3, 4-oxadiazoles via oxidative C–O bond formation. (26th November 2018) - Singh, Dharmender; Tiwari, Sandip Kumar; Singh, Virender
Abstract : An efficient protocol has been developed for one-pot synthesis of biologically interesting β-carboline substituted 1, 3, 4-oxadiazoles via an I2 -assisted oxidative C–O bond formation strategy. Abstract : An efficient protocol has been developed for one-pot synthesis of biologically interesting β-carboline substituted 1, 3, 4-oxadiazoles via an I2 -assisted oxidative C–O bond formation strategy. This metal-free sequential approach is found to be compatible with diversely substituted 1-formyl β-carbolines and aromatic as well as aliphatic hydrazides, providing access to a variety of multifunctional β-carboline linked 1, 3, 4-oxadiazole derivatives in good to excellent yields. The methodology was found to be applicable to gram scale synthesis of β-carboline substituted 1, 3, 4-oxadiazole derivatives. Additionally, β-carboline C1 linked 2-amino-1, 3, 4-oxadiazoles and bis-1, 3, 4-oxadiazoles were also synthesized using the same strategy.